Pemberian Makanan Tambahan Melalui Olahan Jamu Dan Nugget Kelor Sebagai Upaya Pencegahan Stunting - Amalia Khairunnisa; Sutomo Sutomo; Nani Kartinah; Pratika Viogenta; Rizqan Azhari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Stunting is a state of malnutrition and causes delays in brain development and child development in the first 1000 days of life. One of the factors that causes stunting is a lack of nutritional intake in infants or toddler mothers. The purpose of this service is to provide education and practice regarding supplementary feeding through moringa leaves such as nuggets and moringa herbs in Mandiangin Barat village, South Kalimantan. The method used in this service activity is in the counseling about the use of Moringa leaves as processed nutritious food and drinks, as well as the practice of processing Moringa nuggets and herbs. The results of these activities can be concluded that the community in Mandiangin Barat village has developed a level of understanding about supplementary feeding and can process into food and drinks that have nutritional value as an effort to prevent stunting rates in the village.